Distribution locational marginal pricing for congestion management of an active distribution system with renewable-based microgrids under a privacy-preserving market clearing approach and load models. (December 2022) - Babagheibi, Mahsa; Jadid, Shahram; Kazemi, Ahad
Abstract: Microgrid formation has changed the one-direction and passive structure of distribution systems. Increasing the energy demand makes it more sophisticated to keep the operational constraints for the distribution system operator, especially during on-peak hours, which may lead to line congestion. In this study, a distributed locational marginal pricing strategy for congestion management of a radial distribution system with several renewable-based MGs is proposed. The proposed model considers the independent operation for each MG, confidentiality aspects for sensitive data, and the computational burden of problem-solving based on a distributed problem-solving approach. The results show the achievement of the optimal global solution for the feasible problem with more than 99.99% accuracy. Due to the prominent role of load in line congestion, voltage-dependent load models at the distribution system and price-based load models at the MGs side have been considered. The results show that the ignorance of accurate load models can lead to the estimation error for energy trading revenue of MGs up to 29.83% and up to 1.47% for the distribution system compared to non-consideration of load models in a congestion state. Distribution locational marginal prices have also changed by up to 4.18% compared to the case of no-load model considerations. Highlights: Distribution locational marginal pricing strategy for congestion management. Propose a new strategy for renewable-based MGs for market participation. Consider the role of load models in congestion management analysis. Techno-economic analysis for congestion management under day-ahead market.